Management of patients with intermediate stage hepatocellular carcinoma. (November 2020) - Prince, David; Liu, Ken; Xu, Weiqi; Chen, Minjiang; Sun, Jin-Yu; Lu, Xiao-Jie; Ji, Jiansong
Hepatocellular carcinoma (HCC) causes a significant health burden globally and its impact is expected to increase in the coming years. Intermediate stage HCC, as defined by the Barcelona Clinic Liver Cancer (BCLC) system stage B, represents up to 30% of patients at diagnosis and encompasses a broad spectrum of tumor burden. Several attempts have been made to further subclassify this heterogenous group. The current standard of care recommended by BCLC for intermediate stage HCC patients is transarterial chemoembolization (TACE), with modest outcomes reported. While refinements have been made to TACE technique and patient selection, it remains non-curative. In the real-world setting, only 60% of patients with intermediate stage HCC receive TACE, with the remainder deviating to a range of other therapies that have shown promise in select patient subgroups. These include curative treatments (resection, ablation, and liver transplantation), radiotherapy (stereotactic and radioembolization), systemic therapies, and their combination. In this review, we summarize the classifications and current management for patients with intermediate stage HCC as well as highlight recent key developments in this space.